DELAY ON GAIT PATTERNS ON DOWN SYNDROME CHILDREN - Pedro Paulo Deprá; Camila Rinaldi Bisconsini; Lenamar Fiorese Vieira (Journal of Physical Education)
ABSTRACT The main purpose was to compare the spatiotemporal variables of the gait cycle in children with Down Syndrome as a function of age. A longitudinal study was conducted with 20 children, of both genders, aged between 24 and 83 months. Conventional techniques were used in the methodological procedures to record the children's anthropometry and two-dimensional cinematographic techniques for quantification of the spatiotemporal variables of their gait in relation to the global and partial variables. The results showed differences in the behavior of the anthropometric and kinematic variables, stride time, stride frequency, and time of first simple support in children with Down Syndrome between the age of 24-59 months and 60-83 months. The children's gait pattern over the years was established by the changes in frequency instead of the changes in the stride length for the development of gait speed. In conclusion the Behavior modifications in the anthropometric and spatiotemporal variables of the gait in children with Down Syndrome appear to be barely evident between 24 and 59 months of age.